Technostress and counterproductive behaviours in an organisation - Kot, Paweł (Technium Social Sciences Journal, 2022)
Work can be a place where we experience stress. In recent years, employees exposed to work with the use of information and communication technologies have reported symptoms of technostress. In turn, such frustration may lead to various negative and ineffective behaviours at work. The aim of the study was to analyse the links between technostress and counterproductive behaviours (theft, fraud, withdrawal and sabotage). 676 employees (including 50.9% women) aged 20 to 63 (M = 41.04; SD = 13.46) using ICT on a daily basis were surveyed. The study used the Counterproductive Behaviours Questionnaire and the Technostress Creators and Technostress Inhibitors Scale. The obtained results confirmed a positive relationship between Technostress creators and counterproductive behaviours and a negative relationship between Technostress inhibitors and counterproductive behaviours. These results can be used in organisations to minimize the risk of counterproductive behaviours by counteracting the occurrence of Technostress creators and reinforcing Technostress inhibitors.